2002
DOI: 10.1016/s0002-9440(10)64171-5
|View full text |Cite
|
Sign up to set email alerts
|

Expression of IP-10/CXCL10 and MIG/CXCL9 in the Thyroid and Increased Levels of IP-10/CXCL10 in the Serum of Patients with Recent-Onset Graves' Disease

Abstract: Both mRNA and protein expression of the chemokines IP-10/CXCL10 and Mig/CXCL9, as well as of their receptor, CXCR3, were assessed in the thyroid glands of 16 patients suffering from Graves' disease (GD). In addition, IP-10/CXCL10 levels were measured in the serum of 50 GD patients. Expression of IP-10/CXCL10, Mig/CXCL9, and CXCR3 was poor or absent in normal thyroid tissue from patients undergoing thyroidectomy because of primary localized thyroid tumors, while both the chemokines and their receptor were prese… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

14
146
3
4

Year Published

2005
2005
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 152 publications
(167 citation statements)
references
References 43 publications
14
146
3
4
Order By: Relevance
“…Immunohistochemical studies demonstrated high expression of IP-10 in thyroid glands of patients with recent-onset Graves' disease (12,13,17). Thyroid follicular cells as well as infiltrating lymphocytes may be possible sources of IP-10 in sera from patients with newly diagnosed Graves' disease.…”
Section: Discussionmentioning
confidence: 95%
See 2 more Smart Citations
“…Immunohistochemical studies demonstrated high expression of IP-10 in thyroid glands of patients with recent-onset Graves' disease (12,13,17). Thyroid follicular cells as well as infiltrating lymphocytes may be possible sources of IP-10 in sera from patients with newly diagnosed Graves' disease.…”
Section: Discussionmentioning
confidence: 95%
“…In a cross-sectional study, Romagnani et al immunohistochemically demonstrated high expression of CXCR3 and IP-10 proteins in mononuclear cells surrounding follicular structures in thyroid glands from patients with recent-onset Graves' disease, suggesting the importance of a Th1-dominant response in the initial phase of inflammation in this disease (12). However, no previous reports prospectively identified changes in Th1/Th2 balance according to expression of chemokine receptors and their ligands after the patients began treatment.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, the use of the IP-10 ratio might support an improved diagnosis of active TB disease when combined with the standard diagnostic methods, including microbiology, molecular tests, and clinical and radiological assessments. IP-10 (also known as CXCL10 or IFN-␥-induced protein 10) is a chemokine that is expressed at a high level in inflammatory diseases such as systemic lupus erythematosus, thyroid disease, acute coronary syndrome, and allergies (28)(29)(30). IP-10 is expressed in the bronchial epithelium (31) and in inflamed tissues (32) of active TB patients, who demonstrate upregulation of the helper T (Th) 1-type cytokine IFN-␥.…”
Section: Discussionmentioning
confidence: 99%
“…23,24 It has been demonstrated that members of the chemokine superfamily are involved in immunological and autoimmunological diseases. [25][26][27] The upregulation of several chemokines is associated with acute GVHD. 28,29 However, the pathogenic role of chemokines in chronic conjunctival GVHD remains elusive to a large extent.…”
Section: Introductionmentioning
confidence: 99%